JARINGAN TELEKOMUNIKASI PADA SCADA MENGGUNAKAN CISCO PACKET TRACKER - Ragil Febrian; Didik Aribowo; Marcel Ade Satria; Rifqi Badruzzaman (Populer: Jurnal Penelitian Mahasiswa, 2023)
In Indonesia in particular, SCADA has been recognized and started to be implemented in electric power system control since the early 1980s. In other more developed countries, the application of SCADA is growing along with developments in computer and telecommunications technology. At a time when the development of SCADA was not as sophisticated as it is now, there was an idea to make it easier to maneuver, namely in a simple network system using SCADA we can supply additional power or do power outages easily so that the overload does not occur. After implementing the SCADA system there are less time and frequency savings compared to before implementing the SCADA system. This means that the SCADA reliability index is much better after implementing the SCADA system..